Antibiotics and Antibiotic Resistance. - Sköld, Ola (Wiley, 2011)
This book, which is the translated version of a Swedish book, combines a general introduction of a variety of antibiotics with a more in-depth discussion of resistance. The focus on resistance in learning about antibiotics will help future scientists recognize the problem antibiotics resistance poses for medicinal and drug-related fields, and perhaps trigger more research and discoveries to fight antibiotic resistant strains. Current overviews of the topic are included, along with specific discussions on the individual mechanisms (betalactams, glycopeptides, aminoglycosides, etc) used in var.